Methods of Teaching Vocabulary in English Young Learners’ (EYL) Classroom - Lili Sururi Asipi; One Lailla Trisanti; Yasri Tika Damayanti; Viviana Viviana (Journal on Education, 2023)
Vocabulary is a tool for the four skills of speaking, reading, listening, and writing. This research uses qualitative and descriptive methods. This study uses observation and interviews with an English teacher in an elementary school and focuses on the English teacher as an informant about teaching vocabulary methods in English Young Learners' (EYL) classroom. English Young learners' (EYL) are those between the ages of 6 and 12. It is clear from the research findings and discussions in primary schools that teachers use a variety of vocabulary teaching methods, including listen and repeat, listen and do, using songs, and playing games. The iterative, Listen & repeat and listen & do more dominant methods over the others. The solution to this research question is the first significant discovery made by the researchers. There are some inconsistencies between the theoretical and actual methods used by teachers to teach English vocabulary. The methods used in teaching vocabulary in the English Young Learners’ (EYL) classroom very widely. Based on the experience of conducting research, in this section the researcher would like to provide some suggestions that might be useful for further research. Further research development can be further deepened through the case study method and its solutions or through quantitative research, namely investigating English teaching methods and finding new methods in teaching English vocabulary to young learners.